Automated FRET Two‐Hybrid Analysis - Wei, Zhiqiang; Xu, Yanling; Wang, Jingzhen; Sun, Beini; Huang, Qialing; Zhuang, Zhengfei; Chen, Tongsheng; Hu, Min (Journal of biophotonics, 2025)
ABSTRACT The fluorescence resonance energy transfer (FRET) two‐hybrid assay enables live‐cell detection of biomolecular complexes but faces high‐throughput screening (HTS) limitations due to laborious image analysis. We developed an automated platform using the Luminance‐Uniformity‐based Region of Interest Selection (LURS) algorithm, accelerating processing 12‐fold (6 h → 30 min) for three‐channel FRET imaging. Validation with FRET standards (C32V: E D C 32 V = 0.30 ± 0.01 , S C 32 V = 1.06 ± 0.14 ; CVC: E D CVC = 0.40 ± 0.02 , S CVC = 1.90 ± 0.11 ) matched reference values. Applied to Bcl‐xL/Bak interactions under A1331852 treatment, LURS revealed dose‐dependent stoichiometry reduction ( 1.87 → 1.12 ). The method achieved precise signal extraction while preserving native cellular conditions, overcoming throughput constraints in dynamic protein interaction studies. We developed an automated FRET two‐hybrid platform using the LURS algorithm, accelerating image analysis 12‐fold (6 h → 30 min). Validated with C32V/CVC constructs, it accurately measured FRET efficiency and stoichiometry ( n D / n A = 1.06 ± 0.14/C32V; 1.90 ± 0.11/CVC), matching reported values. Applied to Bcl‐xL/Bak interaction under A1331852, it revealed stoichiometry reduction (1.87 → 1.12), enabling HTS‐compatible drug discovery.